PERANAN PROGRAM SIARAN NUMPANG NAMPANG PRO2 LPP-RRI BANDA ACEH - Reni Juliani; Rini Astuti (JIMSI: Jurnal Ilmiah Mahasiswa Ilmu Komunikasi, 2021)
For 2 years the Numpang-Nampang program has become a special program for young people, especially in Banda Aceh. The ride-hailing program has been implemented since 2019 until now. After seeing the phenomena that occur, the purpose of this study is to find out how the role of the passenger broadcast program LPP-RRI Banda Aceh is. The researcher chose to use a qualitative descriptive analysis technique the type of data used in this study is the interview stage, the interviews conducted are by means of a face to face question and answer process with parties who are considered to understand or understand the problems to be researched. The results of the study indicate that the Numpang-Nampang program is a typical flagship program presented by RRI Pro2 88,4 FM Banda Aceh. The Numpang-Nampang program contains information about the lifestyle of young people. The Numpang-Nampang program with a duration of 120 minutes is the flagship program of Pro2 LPP-RRI Banda Aceh, this program has 3 series of broadcast events, including dialogue sessions, cult broadcasts, evening prayer calls, and music programs. Of course the 3 variants of the show in the Numpang-Nampang hailing program make this program very interesting.Keywords: Role, Program, Broadcast Nampang